2015
DOI: 10.1002/lary.25462
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic cochlear implantation: Call for caution

Abstract: 4. Laryngoscope, 126:689-692, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 16 publications
0
17
0
5
Order By: Relevance
“…It is easier to identify the RW with a transcanal approach, but transcanal insertion vector may carry the risk of leading to a more lateral position of the array in the ST and may increase the battery energy needed to stimulate the spiral ganglion neurons. Also, elevating the tympanic annulus carries a significant risk of injury to the annulus or tympanic membrane [ 20 , 31 , 32 ]. We think that transfacial recess endoscopic identification of the RW obviates the need to switch to a transcanal approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easier to identify the RW with a transcanal approach, but transcanal insertion vector may carry the risk of leading to a more lateral position of the array in the ST and may increase the battery energy needed to stimulate the spiral ganglion neurons. Also, elevating the tympanic annulus carries a significant risk of injury to the annulus or tympanic membrane [ 20 , 31 , 32 ]. We think that transfacial recess endoscopic identification of the RW obviates the need to switch to a transcanal approach.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic ear surgery (EES) has gained considerable popularity during the last decade [ 26 , 29 , 31 , 33 , 34 ], and this enthusiasm encouraged the otologists to use endoscopes during conventional and alternative CI surgeries. The first advantage of EES is the endoscopic magnification, which is the growth of the visual field as the endoscope approaches near the object of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Reported advantages of the transcanal endoscopic approach include avoidance of drilling the mastoid cavity, better visualisation of the round window area and safety of the facial nerve. However, in a recent study that analysed the orientation of the cochlear basal turn in relation to the ear canal, it was demonstrated that the trajectory provided by the conventional posterior tympanotomy aligned more favourably with the cochlear basal turn than the transcanal approach, thus may result in less damage caused by deflection of the electrode array in the scala tympani . In addition, it has also been reported that transcanal endoscopic cochlear implantation may lead to late‐onset complications, including electrode extrusion and acquired cholesteatoma in the ear canal …”
Section: Discussionmentioning
confidence: 99%
“…Electrode handling is minimal in case of posterior tympanotomy approach, while in the transcanal approach, the electrode array passes through three bends from transcanal well into the tunnel at its entry, exit from the tunnel, and then through the cochleostomy; complete alignment to the basal turn of cochlea is not possible in all cases. 12,13 Cholesteatoma or severe retraction of pars tensa is a complication which occurs due to injury to the canal wall or tympanic annulus and thin external meatal wall. Bone resorption can lead to migration of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%